Diversity and status of day butterflies (Lepidoptera: Rhopalocera) in different plant associations of the Edough Forest Massif (Northeastern Algeria) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Laref N, Rezzag-Beddida R, Boukheroufa M, Sakraoui R, Henada RLI, Hadiby R, Sakraoui F. 2021. Diversity and status of day butterflies (Lepidoptera: Rhopalocera) in different plant associations of the Edough Forest Massif (Northeastern Algeria). Biodiversitas 23: 954-961. The current study seeks to evaluate the biodiversity and the structure of the Lepidoptera, Rhopalocera stand in the Edough mountain range, Northeastern Algeria. The main objective is to analyse specific and dynamic fluctuations depending on the forest species and assess their functional role. The resulting work was conducted during the 2021 spring season at the Ain Bocal Natural Site, characterized by a succession of four forest species in a sampling corridor approximately 2 km long. The sampling strategy was based on the linear transect method derived from the British BMS Butterflies Monitoring Scheme method, where 390 individuals were counted to calculate and analyse the stand structure parameters. We were also able to carry out the taxonomic identification of 13 species belonging to four families, Pieridae, Nymphalidae, Lycaenidae and Papilionidae. Overall, the results revealed that the Mixed Algerian Oak Forest (Zean Oak Forest) is the richest in species, followed by Cork Oak Forest, Algerian Oak Forest and Maritime Pine Forest. The forest of the Edough, by its composition in habitats and ecological niches, allows the installation of the lepidopterological biodiversity.
Keywords: Forest species, linear transect, Lycaenidae, mountainous massif of the Edough, Nymphalidae, Papilionidae, Pieridae